Sexual Harassment and its Effects in Nepalese Society - A Systematic Review - Palikhe, Amin; Adhikari, Nabin Bahadur; Baral, Rameswor; Bhandari, Rita; Phuyal, Shreeram (Asian Journal of Population Sciences, 2024)
Sexual harassment (SH) is a form of illegal, unwelcome sexual act, and other verbal and physical conduct of a sexual nature in the workplace and other environments. This paper aims to analyze the situation and its effect on Nepalese society. The systematic review procedures were followed using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. This paper has covered to eligible and inclusion of all articles and search databases published on Nepjol, ResearchGate, Taylor and Francis, Mind and Society between 2019 and May 2023, to be written in English, specially, survey relating to the topic of sexual harassment in those open access journal articles. The initial trial and error method was used to select the sample articles at different times, titles and contents. Most of the sexual harassment study was found in Kathmandu Valley targeting the higher school level of female students. The study found that the majority of victims were female, with girls being the most affected by males. The systematic review revealed that the targeted participants were female rather than male. However, there was a sample bias, non-probability sampling techniques, and a lack of inferential research. The findings support that the systematic review identified the common types of it, various perpetrators, and physical, verbal, and non-verbal effects on the victim. Sexually, the majority of victims were female. A systematic review and descriptive research design are limited, with inferential analysis lacking. Policy reviews and surveys are lacking. Future research should focus on preventive measures, policy formulations, and exploring more areas to address sexual harassment and its effects on individuals and society.